Self-made boss : advice, hacks, and lessons from small business owners - Reses, Jackie; Weinberg, Lauren (Chief marketing officer) (McGraw-Hill, 2022)
"From popular startup support company Square comes practical, proven advice to help you launch, manage, and grow your small business Leaders of large businesses rely on boards and their managers for guidance, but entrepreneurs like you have few, if any, experienced advisors to count on. Now, Self-Made Boss provides the community of advisors you need to help make the right decisions every time. Drawn from real-life stories directly from Square's Seller's Community, which is composed of millions of small businesses, the book shows you exactly what works and what doesn't. Told through the eyes of small business owners, Self-Made Boss is filled with rich, colorful examples, and valuable lessons. These are the lessons you learn only when you're an entrepreneur. They include a second-generation ice cream shop owner on how to manage price increases; a NYC restaurant owner on how to hire and manage employees; a Black female roofer on how to break through in a male dominated industry; a dentist who is transitioning out of his business; and stylist who quit her corporate job to pursue her passion. These entrepreneurs share all the things you learn on the job and wish you knew before you started your business. The book provides answers to important questions on a wide variety of topics, including: Turning a personal passion or side hustle into a career Setting up your business for success Getting the word out and build loyalty Building the right team How to transition out of your business and much more With Self-Made Boss you have everything you need to make life and business decisions with knowledge, insight, and confidence"--